Leonard Cohen, the Modern Troubadour - Měsíc, Jiří (Univerzita Palackého v Olomouci, 2021)
This monograph arose from thinking about the literary tradition as described by the Anglo-American modernist writers Ezra Pound and T. S. Eliot. In their view, the tradition of European love-lyrics crystallized in the work of the medieval Occitan troubadours, who represented the cultural and political milieu of the Occitanie of that period and whose work reflected the religious influences of Judaism, Christianity, and Islam.
Keywords: Literární věda